2007
DOI: 10.1121/1.2756759
|View full text |Cite
|
Sign up to set email alerts
|

High frequency ultrasonic characterization of human vocal fold tissue

Abstract: Recently, endolaryngeal sonography at frequencies ranging from 10 to 30 MHz has been found to be useful in diagnosing diseases of the vocal folds (VFs). However, image resolution can be further improved by ultrasound at higher frequencies, necessitating the measurement of high-frequency acoustic properties of VF tissue. The ultrasonic parameters of integrated backscatter, sound velocity, and frequency-dependent attenuation coefficient were measured in both the lamina propria (LP) and vocalis muscle (VM) of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Direct measurement of the acoustic parameters of the vocal folds is another approach. A previous study indicated that the integrated backscatter, attenuation coefficient, and sound velocity were larger for the lamina propria than for the vocal muscle [40], which could have been due to differences between the anatomical structures of the lamina propria and vocal muscle.…”
Section: Application Of Nakagami Imaging To Vocal-fold Characterizationmentioning
confidence: 90%
“…Direct measurement of the acoustic parameters of the vocal folds is another approach. A previous study indicated that the integrated backscatter, attenuation coefficient, and sound velocity were larger for the lamina propria than for the vocal muscle [40], which could have been due to differences between the anatomical structures of the lamina propria and vocal muscle.…”
Section: Application Of Nakagami Imaging To Vocal-fold Characterizationmentioning
confidence: 90%
“…Ultrasonic tissue characterization can also be used to detect small pathological changes in the tumor in addition to observe its size, movement, and the neighboring structure. Therefore, this technique is of important clinical value (Huang et al, 2007;Lai et al, 2007;Mehdi et al, 2007;Saijo et al, 2007).…”
Section: Monitoring Of the Coagulation Change Based On Ultrasonic Tismentioning
confidence: 97%
“…For example, as ultrasound frequency and f-number of the applied transducer are respectively reached to 50 MHz and 2.9, the subsequent axial and lateral resolutions may be increased to 20 and 100 μm, respectively [6]. High frequency ultrasound has been widely used to noninvasively monitor biological tissues, such as the eye, vocal fold, vasculature, blood, skin, heart of small animals, and mice embryos [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%